The diary of Bernard Mark (December 1965 - February 1966) - Nalewajko-Kulikov, Joanna (East european Jewish affairs, 2022)
Ber (Bernard) Mark (1908-1966) was born in Łomża, then Congress Poland. Before the Second World War, he joined the Communist Party of Poland (KPP). He spent the war years in the USSR, where he worked for the Jewish Anti-Fascist Committee and headed the Organizational Committee of Polish Jews. Upon his return to Poland, he became active in Jewish Communist organizations. From 1949 until his death, he served as director of the Jewish Historical Institute (ŻIH), notorious for his pro-Communist version of the Warsaw Ghetto Uprising. After 1956, he distanced himself from his earlier opinions and began to renew ties with the Soviet Jews and Israel. From the early 1960s, he was placed under surveillance by the Security Service (SB). In the last year of his life, Mark kept a diary in Yiddish in which he openly voiced his criticism of current affairs in Poland and Polish-Jewish relations.